Таксономия видов группы fenestralis рода Scenopinus Latr. (Diptera, Scenopinidae) - Кривошеина, Н.П. (Вестник зоологии, 1981)
The data known from literature concerning the most ordinary European speciesof the fenestralis group are analyzed in the paper. Detailed study of the available descriptions permitted specifying characteristics of Scenopinus glabrifrons, S. fenestralis, S. vitripennis and describing Scenopinus ussuriensis sp. n. from the Far East. The latter is most similar to the three above species, according to the body size and appearance, but differs in certain details of the body and genitals structure.